2008
DOI: 10.1634/stemcells.2008-0530
|View full text |Cite
|
Sign up to set email alerts
|

OCT4 Spliced Variants Are Differentially Expressed in Human Pluripotent and Nonpluripotent Cells

Abstract: OCT4 is a master regulator of self-renewal in embryonic stem cells and can potentially encode two spliced variants, designated OCT4A and OCT4B. We have examined the expression pattern of these OCT4 isoforms in various human pluripotent and nonpluripotent cells. Our data revealed that whereas OCT4A expression is restricted to embryonic stem (ES) and embryonal carcinoma (EC) cells, OCT4B can be detected in various nonpluripotent cell types. Furthermore, we detected a novel OCT4 spliced variant, designated OCT4B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
251
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(269 citation statements)
references
References 64 publications
(76 reference statements)
11
251
1
6
Order By: Relevance
“…Notably in this respect, FISH experiments with human MYCN-specific and mouse Cot-1 DNA probes showed that pericytes were always of murine origin (data not shown), similarly to that previously reported in primary NB and in the HTLA-230 pseudometastatic model [8]. As in primary NB, the granular cytoplasmic pattern of Oct-4 staining in orthotopic HTLA-230 tumors prevailed over the nuclear punctate pattern ( Figure 1A-1D) [30]. In order to investigate the immunophenotypic profile of perivascular Oct-4 + NB cells from orthotopic tumors, these cells were tested by immunofluorescence for the expression of panels of stem cell-related, neural progenitor-related and NB-related markers.…”
Section: Identification and Immunophenotypic Characterization Of Oct-supporting
confidence: 85%
See 1 more Smart Citation
“…Notably in this respect, FISH experiments with human MYCN-specific and mouse Cot-1 DNA probes showed that pericytes were always of murine origin (data not shown), similarly to that previously reported in primary NB and in the HTLA-230 pseudometastatic model [8]. As in primary NB, the granular cytoplasmic pattern of Oct-4 staining in orthotopic HTLA-230 tumors prevailed over the nuclear punctate pattern ( Figure 1A-1D) [30]. In order to investigate the immunophenotypic profile of perivascular Oct-4 + NB cells from orthotopic tumors, these cells were tested by immunofluorescence for the expression of panels of stem cell-related, neural progenitor-related and NB-related markers.…”
Section: Identification and Immunophenotypic Characterization Of Oct-supporting
confidence: 85%
“…Oct-4A is specifically involved in stemness maintenance, is highly expressed in human embryonic stem cells and downregulated following differentiation [30]. Oct-4A, together with SOX-2 and NANOG, governs the transcriptional regulatory network by activating expression of pluripotency-related genes and repressing expression of differentiation-related genes [30].…”
Section: Identification Of Oct-4 + Cells In Primary Nb Samples and Nbmentioning
confidence: 99%
“…There are two studies (Tai et al, 2005;He et al, 2012) who had reported Oct4 expression by dysplastic and hyperplastic esophageal mucosa confining to the proliferative zone, and not expressed by the normal mucosa. Oct4 positivity is reported in certain adult tissue including benign endometrial stromal cells (Atlasi et al, 2006;Cauffman et al, 2006;Mathai et al, 2006;Katona et al, 2007;Zangrossi et al, 2007;Atlasi et al, 2008;Forte et al, 2009). We observed slightly higher sensitivity by PCR technique than by the conventional immunohistochemistry method in detecting Oct4 expression, which is similar to other reported data (Atlasi et al, 2006;Xi et al, 2011;.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, OCT4B isoform was detected using isoform specific RT-PCR (not shown). 21 However, the isoform A, specific for embryonic stem cells, was not detectable. These results indicate that neurofibromas contain multipotent cells that may contribute to the tumor formation.…”
Section: Biomarkers For Multipotent Precursors Are Expressed By a Submentioning
confidence: 92%